Rhinological Consequences of Microsurgical Endonasal-Transsphenoidal Surgery for Pituitary Tumors - Hondronikos, Nikolaos; Alomari, Ali; Schrader, Martin; Knappe, Ulrich J (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Transsphenoidal surgery for sellar lesions may affect patency and function of the nasal airways, smell and sinonasal quality of life. Below is our report on otorhinolaryngological data garnered from patients undergoing endonasal transsphenoidal pituitary microsurgery.Methods In a prospective study, 68 patients scheduled for transsphenoidal operations (32 female, 36 male, age 17–72 years) underwent otorhinolaryngological evaluation of their nasal morphology, a standardized smell test (sniffin’ sticks) and rhinomanometry to analyse nasal breathing function preoperatively, 3–5 days postoperatively (without rhinomanometry), after 3–4 months and after 9 months.Results Immediately after surgery, a reduction in smell sensation was detected in almost all patients. Within 3 months, this impairment resolved in all cases except one. In 2 patients (3%) with preoperative anosmia, improvement of smell function to>6 out of 12 sniffin’ sticks was observed. At final visit no patient was noted to have new anosmia. Within 3 months, the results of the rhinomanometry revealed that all patients except one, regained their preoperative nasal breathing function. In 6 patients (8.8%) an improvement in their nose breathing abilities compared to the preoperative state was found. Three patients (4.4%) underwent a LASER transection of mucosal synechiae. In one case with persistent nasal obstruction (1.5%), secondary septoplasty had to be performed. There was no case in which perforation of the nasal septum, nasal tip deflection, or saddle nose deformity was observed.Conclusion Microsurgical resection of pituitary tumors via the endonasal transsphenoidal approach poses an acceptable risk with regards to sinonasal complications. The incidence of secondary rhinosurgical interventions is low. Standardized comparative studies between endoscopic and microsurgical transsphenoidal operations should be undertaken.
Keywords: pituitary surgery; sinonasal outcome; nasal synechia; hyposmia; quality of life